The effectiveness of garlic extract (Allium sativum linn) in controlling aflatoxicosis in laying hens - Maryam, Romsyah; Sani, Yulvian; Juariah, Siti; Firmansyah, Rachmat; ., Miharja (Indonesian Animal Sciences Society, 2003)
Aflatoxicosis is a disease generated as the consequence of aflatoxin contamination in foods and feeds. Garlic (Allium sativum Linn.), a natural spice known to reduce the toxicity of aflatoxins in poultry. Twenty five laying hens were used to study the effectiveness of garlic extract in reducing aflatoxicosis. The animals were divided into 5 groups i.e (1) control group, (2) group treated with 0.4 mg/kg BH, (3) group treated with 0.4 mg/kg BH and 4% garlic extract in feed, (4) group treated with 5 mg/kg BH, and (5) group treated with 5.0 mg/kg BH and 4% garlic extract in feed. Body weight gains, eggs production, and the activity of glutamate oxaloacetate transaminase (GOT), glutamate pyruvate transaminase (GPT), and Î³-glutamytransferase (Î³- GT) enzymes were observed every week. The residue levels of the aflatoxin and metabolites were measured in the eggs using high performance liquid chromatography (HPLC). The results indicated that group treated with 0.4 mg AFB1/kg BH dan 5.0 mg AFB1/kg BH resulted in decreasing body weight gains, egg production, and increasing the level of GOT, GPT and Î³-GT. The addition of 4% garlic extract in the feed was effective to improve the body weight gain and egg production only in the group of chicken treated with 0.4 mg AFB1/kg BH. However, it decreased the enzymes activities of the GOT, GPT, and Î³-GT, as well as reduced the aflatoxin residues and metabolites in the groups at both aflatoxin levels (0.4 and 5.0 mg/kg BH). Aflatoxin residues decreased up to 42.2% for the group treated with the low dose of AFB1 (0.4 mg/kg) and 49.0% for the group treated with the high dose of AFB1 (5 mg/kg). Â Key words: Garlic, aflatoxicosis, laying hens, aflatoxin residues